Designing story card in extreme programming using machine learning technique - Yasin, Azman; Gaber, Shamsan; Omar, Mazni; Mohd, Haslina; Baharom, Fauziah; Md Din, Marina (2012)
Story card is one of the software development artifacts that can be used to gather requirements in extreme programming (XP).It can assists developers to translate and develop the system based on activities and rules stated in the story card.However, conventional XP story card framework or template is not well defined and only supports requirements in two or three sentences.It also does not states any information rather than system functionality.This may lead to conflicts, missing, and ambiguous requirements.In order to overcome this problem, Machine Learning is one of the techniques that can be used to extract the content from the list of requirements and produce the story cards based on the priority and rules of requirements.Thus, this study aims to to propose a new technique of designing story cards based on user requirements.The finding from the study is a conceptual model of designing story cards using machine learning technique.Future research will investigate how the technique adapt with the iterative changes of the requirements.